HUBUNGAN PENGETAHUAN DAN LAMA WAKTU KERJA PADA IBU MENYUSUI YANG BEKERJA DENGAN PEMBERIAN ASI EKSKLUSIF DI PT. CELEBES MINAPRATAMA WANGURER TIMUR KOTA BITUNG - deviana pratiwi munthe (Jurnal Mutiara Kesehatan Masyarakat, 2020)
Abstrak Exclusive breastfeeding for babies aged 0-6 months is highly recommended because breast milk is a source of energy and nutrition, especially for babies. After all, it contains perfect milk and is beneficial for the baby's growth and development. But many breastfeeding mothers are unable to provide exclusive breastfeeding to their babies due to several factors, including the mother's knowledge of the benefits of breastfeeding and the length of time the mother works outside the home. Exclusive breastfeeding in North Sulawesi Province is the second-lowest nationwide, which is only 38.69%. In 2014 the number of babies who were exclusively breastfed was 38.5%, while in 2015 it decreased to 33.5%. This type of research uses quantitative using a cross-sectional approach. The analysis used is the Chi-Square statistical test. Sampling in this study using a total sampling of 67 people. The results of this study are the knowledge of mothers about exclusive breastfeeding with exclusive breastfeeding at PT. PT. Celebes Minapratama Wangurer Timur obtained poor knowledge of 41 people (61.2%). The results of statistical tests obtained p-value = 0.048, it can be concluded that there is a relationship between knowledge of working breastfeeding mothers and exclusive breastfeeding at PT. Celebes Minapratama Wangurer Timur Bitung City. The length of time the mother worked outside the home > 8 hours was 46 people (68.7%). The results of statistical tests obtained p-value = 0.015. So it can be concluded that there is a relationship between the length of time working for breastfeeding mothers who work and exclusive breastfeeding at PT. Celebes Minapratama Wangurer Timur Bitung City. Keywords: Exclusive Breastfeeding, Knowledge, Working Time